The Pilotage Policy Paradox: Competency Gaps and Maritime Education Reform in Indonesia - Anggita Aryati; Marihot Simanjuntak; Irfan Faozun (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Indonesia's policy delegating pilotage services to Port Business Entities (BUPs) aims to enhance efficiency and Non-Tax State Revenue (PNBP). While quantitative Key Performance Indicators (KPIs) at six BUPs show "very good" performance, this qualitative multiple-case study reveals this success as a "façade." Through in-depth interviews with BUP management, regulators (KSOP), and pilots, the research uncovers significant operational friction stemming from critical competency gaps. Although personnel possess high technical proficiency based on STCW standards, they lack essential non-technical skills in commercial law, service management, and public financial governance required by the new delegation policy. The perceived "very good" performance is unsustainably achieved through informal workarounds and individual heroic efforts rather than efficient systemic processes. This study diagnoses the policy-practice gap as a systemic educational failure. The findings provide evidence-based recommendations for urgent curriculum reform in Maritime Education and Training (MET) to integrate critical managerial and administrative competencies. This alignment is essential for transitioning from traditional state-bureaucratic models to modern market-oriented port governance, ensuring that human resource development keeps pace with regulatory evolution in the maritime sector.